Comparison of The Effectiveness of Use Antiseptic Povidone Iodine 10% And Octenidine Hydrochloride 0.1% in The Action of Neuroaxial Blocks in Patients Who Will Surgery in Haji Adam Malik General Hospital Medan - Handayani, Bejo Utomo; Bisono, Luwih; Wijaya, Dadik Wahyu; Amelia, Rina (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2025)
Background: Antiseptics or germicides are chemical compounds used to kill or inhibit the growth of microorganisms on living tissue such as the surface of the skin and mucous membranes.Objective: To determine the comparative effectiveness of povidone iodine 10% antiseptic compared to octenidine hydrochloride 0.1% in neuraxial blockade in patients undergoing surgery at Haji Adam Malik General Hospital, Medan.Methods: This study is an experimental study of the two-group pre-test - post-test study type. This design is a design that groups patients into certain groups that receive different treatments based on group division. There are two groups, with each group containing 10 samples.Result: In group A (povidone iodine 10%), the average value of bacterial growth before aseptic action was 192.20±117.54, and after aseptic action, no bacterial growth was found with a P Value of 0.005. In group B (octenidine hydrochloride 0.1%) before aseptic action was performed, the average bacterial growth value was 212.20 ± 107.21, and after aseptic action, no bacterial growth was found with a P Value of 0.004.Conclusion: There was no significant difference in the bacterial profile after aseptic with povidone iodine 10% and octenidine hydrochloride 0.1%.